2009
DOI: 10.1177/1074248409349620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Targeting Mitogen-Activated Protein Kinase on Cardiac Remodeling in Rats

Abstract: Targeting MAPK might represent a useful therapeutic avenue to ameliorate cardiac remodeling and support the notion that atRA and statins are potential candidates for the prevention and therapy of cardiac remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For instance, in the heart, atorvastatin increases phosphorylation of a host of mediators associated with NO signalling, such as ERK, PDK‐1, Akt and eNOS itself, plausibly via an adenosine receptor‐dependent mechanism (Merla et al ., ; Ye et al ., ). Direct modulation of NO signalling by statins downstream of NOS was also suggested by another study, where rosuvastatin administration reverted the elevation in mean arterial blood pressure and cardiac remodelling caused by a treatment with a NOS inhibitor, L‐NAME (Baraka et al ., ). Statins modulate cardiac NO metabolism under hyperlipidaemic conditions as well.…”
Section: Interaction Of Pharmacological Treatment Of Metabolic Syndromentioning
confidence: 97%
“…For instance, in the heart, atorvastatin increases phosphorylation of a host of mediators associated with NO signalling, such as ERK, PDK‐1, Akt and eNOS itself, plausibly via an adenosine receptor‐dependent mechanism (Merla et al ., ; Ye et al ., ). Direct modulation of NO signalling by statins downstream of NOS was also suggested by another study, where rosuvastatin administration reverted the elevation in mean arterial blood pressure and cardiac remodelling caused by a treatment with a NOS inhibitor, L‐NAME (Baraka et al ., ). Statins modulate cardiac NO metabolism under hyperlipidaemic conditions as well.…”
Section: Interaction Of Pharmacological Treatment Of Metabolic Syndromentioning
confidence: 97%
“…Previous studies have shown that patients with obesity display increased levels of C-reactive protein (CRP) and IL-6 compared to the controls (Ellulu et al, 2016;Okamoto et al, 2015). In addition, the activation of p38MAPK has been correlated with myocardial remodeling (Yoshida et al, 2001;Baraka et al, 2009;Yu et al, 2012). p38MAPK can be activated by a variety of stimuli, such as elevated levels of free fatty acids, cholesterol, glucose, and proinflammatory mediators (Ragheb et al, 2009;Shalini et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…p38MAPK can be activated by a variety of stimuli, such as elevated levels of free fatty acids, cholesterol, glucose, and proinflammatory mediators (Ragheb et al, 2009;Shalini et al, 2016). Moreover, the activation of p38MAPK can regulate gene expression, which may promote myocardial remodeling (Baraka et al, 2009).…”
Section: Introductionmentioning
confidence: 99%